2021
DOI: 10.1080/14763141.2021.1959946
|View full text |Cite
|
Sign up to set email alerts
|

How do swimmers control their front crawl swimming velocity? Current knowledge and gaps from hydrodynamic perspectives

Abstract: The aim of this study was to review the literature on front crawl swimming biomechanics, focusing on propulsive and resistive forces at different swimming velocities. Recent studies show that the resistive force increases in proportion to the cube of the velocity, which implies that a proficient technique to miminise the resistive (and maximise the propulsive) force is particularly important in sprinters. To increase the velocity in races, swimmers increase their stroke frequency. However, experimental and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…In front crawl swimming, the arms exert greater propulsive force than the legs (Cohen et al, 2017 ), and of the upper arms, forearms and hands, it has been suggested that the hands exert the largest propulsive force (Toussaint et al, 2002 ; Samson et al, 2017 ; Takagi et al, 2021 ). Therefore, the present experiment was conducted based on the assumption that the force exerted by the segments other than the hand would be negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In front crawl swimming, the arms exert greater propulsive force than the legs (Cohen et al, 2017 ), and of the upper arms, forearms and hands, it has been suggested that the hands exert the largest propulsive force (Toussaint et al, 2002 ; Samson et al, 2017 ; Takagi et al, 2021 ). Therefore, the present experiment was conducted based on the assumption that the force exerted by the segments other than the hand would be negligible.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the arms exert more propulsion than the legs in front crawl swimming (Cohen et al, 2017 ) and that the hands contribute the most propulsion among the upper arm, forearm and hand (Toussaint et al, 2002 ; Samson et al, 2017 ; Takagi et al, 2021 ). Hence, the magnitude of propulsion in hand is related to swimming velocity (Tsunokawa et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Both male and female breaststroke-specialists showed a 3.0–4.5% faster clean-swimming speed during the third lap of their 200 m race compared to IM swimmers’ breaststroke lap. Swimming speed is the product of distance per stroke and stroke rate [ 14 , 15 ], and swimmers generally control their speed by increasing stroke rate rather than distance per stroke [ 16 , 17 ]. In other words, higher stroke rate increases exercise intensity, thus energy cost, which is the energy expenditure required to swim a given distance [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent work of Takagi et al [16] reviewed the literature on front crawl, focusing on propulsive and resistive forces at different swimming velocities. The relationships between energetic, biomechanical, and fluid dynamics indices in competitive swimming were established factors that determine the mean of the instantaneous magnitudes of hand velocity over some time.…”
Section: Related Workmentioning
confidence: 99%